Opportunistic oral infections in patients submitted to radiotherapy for head and neck cancer: a retrospective study (Research, Society and Development, 2020)
To evaluate retrospectively the prevalence of opportunistic oral infections in head and neck cancer patients submitted to radiotherapy, in combination or not with chemotherapy and surgery. The survey was performed by revision of electronic medical records of patients submitted to 3D-conformational RT for head and neck cancer from the Record Book of Medical Physics of Radiotherapy Division at Federal University of São Paulo (São Paulo Hospital), considering personal and clinical data. Among the 79 patients evaluated, 38 developed an opportunistic oral infection. Besides, most of them were white men, younger than 60 years, ex-smokers, ex-alcoholic, and underwent dental treatment pre-RT. The most frequent histological type was the squamous cell carcinoma and the most affected anatomical site was the larynx. There were also higher rates of stage IV tumors and oncologic treatments performed with a combination of RT, chemotherapy, and surgery. In relation to the opportunistic oral infections, candidiasis was the most representative. Patients with advanced-stage head and neck cancer seem to present oral candidiasis more frequently, probably due to the multimodal treatment.